Pengukuran Tingkat Kepuasan Pelanggan Terhadap Kualitas Pelayanan Jasa Transportasi Menggunakan Metode SERVQUAl Dan PGCV (Potential Gain In Customer Value) (Studi Kasus: BPU. Rosalia Indah) - Adi Nugroho, Rachmad; , Mila Faila Sufa, S.T., M.T; , Ratnanto Fitriadi, S.T., M.T (2015)
Research on the BPU. BEAUTIFUL ROSALIA is done with the purpose of: (1) Determine the quality of service in Palur agency headquarters, agency mill, Kartasura agent at the BPU. ROSALIA BEAUTIFUL. (2) Knowing the variables of service that should be prioritized in order to repair the level of passenger satisfaction with quality of services in mass transportation services provided by the BPU. ROSALIA BEAUTIFUL. (3) Make proposals on the improvement of quality of service in BPU. ROSALIA BEAUTIFUL through the application of methods SERVQUAL and Potential Gain in Customer Value (PGCV). Basically SERVQUAL is a comparison of two main factors, namely real customer perception of the service they receive with the service actually expected / desired. Its definition if the reality is greater than expected, then the said service quality, and vice versa if the reality is less than expected, then the service is said to be inferior. If fact the same as it is said to satisfy expectations. Potential gain for the index in Customer Value (PGCV) is a concept to determine the attributes that should be prioritized in order to improve quality of service. The results showed that the SERVQUAL calculation indicates the level of satisfaction with the fact that the customer received an average given was satisfactory (3.05), but not in accordance with the expectations of the average level of expectations of customers, namely (4.39). Results using index Potential Gain in Customer Value (PGCV) indicates that the service attributes that should be prioritized to improve the level of passenger satisfaction is the existence of compensation in case of delay bis (9.27), Timeliness itinerary (9.23), safety and comfort while in agent (9.07), condition of the agency comfortable, neat and clean and the room layout good agent (9.01), Agents provide services in accordance with the commitments (8.72), Staff be patient in serving customers (8.69).